2020
DOI: 10.3390/cancers12071979
|View full text |Cite
|
Sign up to set email alerts
|

DCE-MRI of Tumor Hypoxia and Hypoxia-Associated Aggressiveness

Abstract: Tumor hypoxia is associated with resistance to treatment, aggressive growth, metastatic dissemination, and poor clinical outcome in many cancer types. The potential of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) to assess the extent of hypoxia in tumors has been investigated in several studies in our laboratory. Cervical carcinoma, melanoma, and pancreatic ductal adenocarcinoma (PDAC) xenografts have been used as models of human cancer, and the transfer rate constant (Ktrans) and the extrava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 49 publications
3
13
0
1
Order By: Relevance
“…The numerical values of the constants in the Lund arterial input function were as follows: A = 5.10 mM, B = 14.2 s −1 , C = 0.99 mM, and D = 0.159 s −1 ( 22 ). Plots of Gd-DTPA concentration versus time and the corresponding model fits for individual voxels in the human tumors have been reported previously ( 22 , 33 ), and illustrate that the quality of the DCE-MRI acquisition and analysis was sufficient to produce good model fits. After DCE-MRI, the patients were treated with concurrent cisplatin-based chemoradiation therapy with curative intent.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…The numerical values of the constants in the Lund arterial input function were as follows: A = 5.10 mM, B = 14.2 s −1 , C = 0.99 mM, and D = 0.159 s −1 ( 22 ). Plots of Gd-DTPA concentration versus time and the corresponding model fits for individual voxels in the human tumors have been reported previously ( 22 , 33 ), and illustrate that the quality of the DCE-MRI acquisition and analysis was sufficient to produce good model fits. After DCE-MRI, the patients were treated with concurrent cisplatin-based chemoradiation therapy with curative intent.…”
Section: Methodssupporting
confidence: 66%
“…Plots of Gd-DOTA concentration versus time and the corresponding model fits for individual voxels in BK-12, ED-15, HL-16, and LA-19 tumors have been reported previously and illustrate the quality of the DCE-MRI acquisition and analysis ( 12 ). The time resolution was sufficient to produce good model fits using Tofts generalized pharmacokinetic model and the population-based arterial input function, but was too low to measure individual arterial input functions in large arteries within the field of view and for using Tofts extended pharmacokinetic model which includes the contribution from intravascular contrast agent ( 18 , 33 ). Tumors were resected for histological examination immediately after DCE-MRI.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxia and the endoplasmic reticulum stress response Hypoxia. Cells in solid tumors are exposed to hypoxic conditions, and extensive hypoxia is correlated with platinum resistance and tumor progression [55]. Hypoxic transcriptional programs are mainly activated by the HIF transcription factors but can also be activated by other stress signaling pathways.…”
Section: Alterations In Pleiotropic Processes and Pathwaysmentioning
confidence: 99%
“…Also, chronic hypoxia, as well as transient changes in pO 2 , are affected not only by oxygen supply (perfusion) but also by a variety of factors, including hemoglobin saturation and vascular architecture. Recently, Gaustad et al showed that the Ktrans parameter derived from DCE-MRI compartmental analysis data is associated with tumor hypoxia in xenograft models of cervical carcinoma, melanoma, and pancreas ( 190 ). We present in Figure 4 an example of multimodality imaging of a patient with head and neck cancer.…”
Section: Medical Imagingmentioning
confidence: 99%